2006
DOI: 10.1128/iai.74.2.1266-1272.2006
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax Lethal Toxin Induces Ketotifen-Sensitive Intradermal Vascular Leakage in Certain Inbred Mice

Abstract: Bacillus anthracis lethal toxin (LT) is a bipartite toxin composed of protective antigen (PA) and lethal factor (LF). Injection of LT produces clinical signs characteristic of anthrax infection, including pleural edema and vascular collapse in various animal models. We utilized the classic Miles leakage assay to quantify vascular leakage in mice. LT injected intradermally induced leakage as early as 15 to 25 min in some inbred mouse strains, but not in others, whereas PA or LF individually did not induce leaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 39 publications
5
55
1
Order By: Relevance
“…Recent studies using endothelial cells in culture have reported LeTx induced apoptosis or barrier dysfunction, depending on the particular endothelial cell type and treatment (12,16,17). Our model exposes endothelial cells to LeTx within the context of intact, lumenized, and functional blood vessels.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Recent studies using endothelial cells in culture have reported LeTx induced apoptosis or barrier dysfunction, depending on the particular endothelial cell type and treatment (12,16,17). Our model exposes endothelial cells to LeTx within the context of intact, lumenized, and functional blood vessels.…”
Section: Resultsmentioning
confidence: 96%
“…Early reports indicated that EdTx did not produce significant mortality (9), but recently robust effects have been reported, including lethality in rodents (10,11). However, the ability to induce loss of vascular integrity and leakage has been consistently associated with LeTx (7,(10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular leakage in mouse models shows similar results using a Miles assay, which uses intravenously-delivered Evan's blue dye to quantify macromolecular vascular leakage. Subcutaneous injection of purified LT results in a rapid (15-25 minutes) and dose dependent response in mice [255]. This rapid response to LT suggests that vascular leakage is due to a transcription/translation independent event.…”
Section: Cardiovascular and Endothelial Effectsmentioning
confidence: 99%
“…The fact that ketotifen, a histamine inhibitor, can greatly reduce the amount of leakage lends credence to this idea, though it is uncertain via which mechanism or on which cell ketotifen is functioning. The ability and degree of leakage varies between inbred mice strains and has no correlation to strain susceptibility to LT-mediated death [255]. Therefore, LT mediated death may be due both to vascular leakage and the host's response to the leakage.…”
Section: Cardiovascular and Endothelial Effectsmentioning
confidence: 99%